THE EFFECT OF GUANO COMPOST AND COMPOST TYPES ON THE GROWTH AND YIELD OF CAISIM MUSTARD (Brassica juncea L.) IN DRY LANDS - Nahak, Maria Ernaldis Bano; Bria, Deseriana; Mata, Meri Helsiana; Naisali, Hyldegardis (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This research was carried out in September-November 2025 in the Greenhouse and continued at the Laboratory of the Faculty of Agriculture, Science and Health, University of Timor, Sasi Village, Kota Kefamenanu District, North Central Timor Regency, East Nusa Tenggara Province. The most dominant problems in dry land areas include lack of water, acidic soil reaction, lack of nutrients, cation exchange capacity and shallow soil solum. This study aims to examine the effect of providing guano compost tea and types of compost on the growth and yield of caisim mustard greens in dry land.Data analysis using the SAS 9.1 program. The findings showed that the interaction between guano compost tea and the type of compost had a significant effect on plant height at 7 days after planting, observations of the number of leaves at 14 and 21 days after planting and the total fresh weight of the plants. A single treatment of compost tea had a significant effect on plant height at 21 and 28 HST, shoot fresh weight, root fresh weight, root length and root dry weight with the best treatment being 300 ml of guano compost tea. The single treatment of compost type had a significant effect on the observation of plant height at 7, 14, 21, 28 HST, observation of the number of leaves at 14, 21, 28 HST, fresh weight of the crown, fresh weight of the root, root volume, dry weight of the crown, dry weight of the root and harvest index with the best treatment at K1: 1.5 kg of soil + 1.5 kg of biochar compost.  Keywords: Crop yield, Compost types, Dry land, Mustard greens, Guano compost tea, Mustard greens